2014
DOI: 10.1126/science.1257156
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for direct molecular oxygen production in CO 2 photodissociation

Abstract: Photodissociation of carbon dioxide (CO2) has long been assumed to proceed exclusively to carbon monoxide (CO) and oxygen atom (O) primary products. However, recent theoretical calculations suggested that an exit channel to produce C + O2 should also be energetically accessible. Here we report the direct experimental evidence for the C + O2 channel in CO2 photodissociation near the energetic threshold of the C(3P) + O2(X3Σg–) channel with a yield of 5 ± 2% using vacuum ultraviolet laser pump-probe spectroscopy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
89
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(91 citation statements)
references
References 34 publications
2
89
0
Order By: Relevance
“…2.7 Ga) surface environment, supporting oxidative elemental cycling (Anbar et al, 2007; Kendall et al, 2010; Stolper et al, 2010; Crowe et al, 2013; Lalonde and Konhauser, 2015; Frei et al, 2016). These oxygen traces or the consequences of these oxidative processes could have resulted from abiotic reactions such as CO 2 photodissociation (Lu et al, 2014) and H 2 O 2 disproportionation (Haqq-Misra et al, 2011), but also from biological processes like benthic oxygenic photosynthesis (Lalonde and Konhauser, 2015). Atmospheric oxygen accumulation, however, did not occur at a global scale before the Great Oxidation Event around 2.33 Ga ago (Bekker et al, 2004; Kaufman et al, 2008; Konhauser et al, 2009; Lyons et al, 2014; Luo et al, 2016).…”
Section: Evolution Of the Biogeochemical Conditions In Ancient Oceansmentioning
confidence: 99%
“…2.7 Ga) surface environment, supporting oxidative elemental cycling (Anbar et al, 2007; Kendall et al, 2010; Stolper et al, 2010; Crowe et al, 2013; Lalonde and Konhauser, 2015; Frei et al, 2016). These oxygen traces or the consequences of these oxidative processes could have resulted from abiotic reactions such as CO 2 photodissociation (Lu et al, 2014) and H 2 O 2 disproportionation (Haqq-Misra et al, 2011), but also from biological processes like benthic oxygenic photosynthesis (Lalonde and Konhauser, 2015). Atmospheric oxygen accumulation, however, did not occur at a global scale before the Great Oxidation Event around 2.33 Ga ago (Bekker et al, 2004; Kaufman et al, 2008; Konhauser et al, 2009; Lyons et al, 2014; Luo et al, 2016).…”
Section: Evolution Of the Biogeochemical Conditions In Ancient Oceansmentioning
confidence: 99%
“…However, theoretical simulations suggested the possibility of generating O 2 through the dissociation of a CO 2 molecule [4]. A recent experiment showed the evidence of O 2 formation from CO 2 molecules after UV excitation through the detection of C + [5]. So far, O 2 formation from CO 2 has not been directly observed.…”
mentioning
confidence: 99%
“…The dynamics of these reactions is not mediated by a single conventional TS associated with an SP of index one. [7,[11][12][13][35][36][37][38][39][40] For this reason it is important to have a method that explores a region of a PES where an SP 2 emerges. The GAD method is a potential algorithm to be used for this aim.…”
Section: Search Of Sp's Of Higher Index By Gad Trajectoriesmentioning
confidence: 99%
“…Such non-RP dynamics may well be the rule rather than the exception for hot molecules. [7][8][9][10][11] Recently, theoretical work has suggested that a hint for many of these non-RP processes is a "secondindex saddle point" (SP 2 ) on the PES. The index is the number of unstable directions attached to the saddle.…”
mentioning
confidence: 99%